Drinking Location and Pregaming as Predictors of Alcohol Intoxication Among Mandated College Students. (2nd July 2016) - Miller, Mary Beth; Borsari, Brian; Fernandez, Anne C.; Yurasek, Ali M.; Hustad, John T. P.
ABSTRACT: Background : Both drinking location and pregaming have been associated with heavy alcohol use among college students, yet the manner by which they uniquely contribute to alcohol intoxication remains unclear. Objective : The current study examined the unique utility of drinking location and pregaming in predicting alcohol intoxication among college students who violated campus alcohol policy. Method : Between 2011 and 2012, mandated college students who reported drinking prior to their referral events ( N = 212, 41% female, 80% White, M age = 19.4 y) completed a computerized assessment of drinking location and related behaviors as part of larger research trial. Chi-squared statistics, t-tests, one-way analyses of covariance, and regression were used to examine study aims. Results : Participants were most likely (44%) to report drinking in off-campus housing prior to the referral event, and approximately half (47%) reported pregaming. Alcohol intoxication on the night of the referral event differed significantly as a function of both drinking location and pregaming, but pregaming did not moderate the association between drinking location and alcohol intoxication among mandated students. Female birth sex, pregaming, and drinking at either fraternities or off-campus housing predicted greater levels of alcohol intoxication on the night of the referral incident, while drinking in a residence hall/dorm predicted lower intoxication. Conclusions/Importance: Drinking location and pregaming are distinct predictors of alcohol intoxication among mandated college students. Future interventions may benefit from targeting both where and how college students consume alcohol.